Ethical Aspects of Climate Engineering - Betz, GregorCacean, Sebastian (KIT Scientific Publishing, 2012)
This study investigates the ethical aspects of deploying and researching into so-called climate engineering methods, i.e. large-scale technical interventions in the climate system with the objective of offsetting anthropogenic climate change. The moral reasons in favour of and against R&D into and deployment of CE methods are analysed by means of argument maps. These argument maps provide an overview of the CE controversy and help to structure the complex debate.
English
Keywords: climate engineering; climate ethics; ethics; argument map; geoengineering